Children with alcohol intoxication in Cracow, Poland. Issue 2 (2nd April 2016) - Kościelniak, Barbara; Tomasik, Przemysław J.
ABSTRACT: Alcoholism among minors is a serious social problem. The aim of the current study was to analyze alcohol intoxication in children based on hospitalizations in the University Children's Hospital in Cracow between the years 2007 and 2015. During these 9 years, 381 patients were hospitalized due to excessive alcohol consumption. Most patients were junior high school or high school students. The highest blood alcohol concentrations in hospitalized patients were found in a 16-year-old boy (BAC .41%) and a 15-year-old girl (BAC .37%). Alcohol consumption and severe intoxication are linked to a wide variety of familial, social, and personal problems.